Efficiency of the agricultural commodity futures market by applying the cointegration test - Harzer, Jorge Harry; Costa, Carol Thiago; da Silva, Wesley Vieira; Souza, Alceu (Revista de Administração da UFSM, 2012)
This article aims at testing the weak form of efficiency of the commodity futures market in Arabica coffee farming using the cointegration technique in order to check if the current futures prices are biased estimators of spot prices expected for the future. Thereto it uses the futures prices time series from January 2005 to May 2011, which were collected in the Commodities and Futures Exchange - BM & F and spot prices, calculated by CEPEA / ESALQ / USP. Dickey and Fuller’s ADF tests are the metrics used to detect the presence of unit root and Johansen’s cointegration test is used to verify the existence of a long term relationship. The results indicated the non-stationarity of price series besides the presence of cointegration. However, regression parameters testing α = 0 e β = 1 proves that weak efficiency and non-biased found statistical evidence of non-market efficiency. Moreover, the presence of a bias indicating the existence of a premium associated with risk was also found.